Tritirachium oryzae and Other Endophytic Mediated Jambu Bol (Syzygium malaccense) are Potential as an Antioxidant - Hapida, Yustina; Elfita, Elfita; Widjajanti, Hary; Salni (Science and Technology Indonesia, 2022)
Natural bioactive substances have been discovered produced of intracellular fungi. Intracellular fungi, as well as endophytic fungi, it can be found in organs are leaves, stems, roots, fruits, flowers, and seeds. This study aimed to specify for antioxidant activity of intracellular fungi Jambu Bol (Syzygium malaccense) mediated and identify secondary metabolites compounds. The liquid culture was partitioned with ethyl acetate solvent. Using chromatographic techniques, extracts were separated from their secondary metabolites with antioxidant activity apply the DPPH procedure. Its chemical structure was determined using NMR spectroscopic research, and endophytic fungi were recognized using phenotypic characteristics and molecular classification. The endophytic fungus isolation yielded four isolates: YF11, YF12, YF13, and YF14. YF12, with an IC50 of 53.03 g/mL, was the fungus that exhibited good antioxidant activity. Pure chemical secondary metabolites compounds were identified as 2-(4-hydroxyphenyl)-4-methoxytetrahydrofuran-3-ol. Tritirachium oryzae was identified as the endophytic fungus YF12 based on morphological studies and a phylogenetic tree. To boost its antioxidant activity, more study is needed to perform a semi-synthetic reaction on this pure molecule